The Turning point - Laurents, Arthur; Laurents, Arthur; Ross, Herbert; Ross, Herbert (20th Century Fox Home Entertainment, 1977)
It is partly based on the life of dancer Leslie Browne, who portrays Shirley MacLaine's daughter. Her co-star and colleague at the American Ballet Theatre, the great Russian dancer Mikhail Baryshinov, made his screen debut as a dramatic actor in the film.